EMBRACE: One Small Story in Lupus—One Giant Challenge in Clinical Trials. Issue 9 (24th June 2022) - Sheikh, Saira Z.; Englund, Tessa R.; Burriss, Susan W.; Bull, Jonca; Harry, Anya; Groark, James G.; Hall, Ashley M.; Miller, Michelle; Roth, David A.
Abstract : Clinical trials of novel therapeutics in the United States have not been adequately representative of diverse populations, particularly racial and ethnic minorities. The challenges and consequences of underrepresentation in clinical trial recruitment are exemplified by the case of belimumab, a biologic treatment for systemic lupus erythematosus (SLE), a disease that is more prevalent in patients of Black African ancestry and of Hispanic/Latino ethnicity than in other patient populations. Although belimumab was found to be effective in phase 2 and 3 clinical trials in the general population, post hoc analyses of efficacy data in patients of Black African ancestry showed inconsistent results. Consequently, a cautionary statement regarding belimumab use in this population was added to the product label. To alleviate concerns that belimumab may not be safe and effective for patients of Black African ancestry, the Efficacy and Safety of Belimumab in Black Race Patients with SLE (EMBRACE) study was conducted in a post‐marketing commitment to the Food and Drug Administration. The study recruited only patients who self‐identified as being of Black race; its findings led to the removal of the cautionary labeling of belimumab use in patients of Black African ancestry. Our manuscript highlights the critical lessons learned from the successes and failures of the EMBRACE study. It also provides suggestions for overcoming health disparities, highlighting strategies for conducting well‐designed clinical trials to overcome systematic barriers to diversity in recruitment, with a focus on enacting long‐term support to ensure equity in the process, products, and benefits from drug development and clinical trials.